PHYTOCHEMICAL CHARACTERIZATION OF A BIFLAVONOID FRACTION FROM Garcinia madruno: INHIBITION OF HUMAN LDL OXIDATION AND ITS FREE RADICAL SCAVENGING MECHANISM - OSORIO D., Edison; Montoya P., Guillermo; Bastida, Jaume (Vitae, 2009)
The inhibitory LDL oxidation potential and free radical stabilization capacity of a characterized biflavonoid fraction (FB) was evaluated and correlated by its biflavonoid content. Morelloflavone, volkensiflavone and amentoflavone were identified in the FB. The extract containing the FB (AcOEt extract) was found to be the major contributor to the free radical-scavenging activity of G. madruno. The DPPH activity for the FB was 4.50 μg/mL. Lipid peroxidation, induced with CuSO4, was significantly reduced in the presence of the FB (CE50 = 11.85 μg/mL). Morelloflavone was found to be the main biflavonoid in the fraction responsible for its protection against lipid peroxidation and free radical-scavenging activity, although processes of synergy are possible. These properties suggest that the FB of G. madruno is an excellent candidate for use as an antioxidant.